2012
DOI: 10.1186/1742-2094-9-230
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal toll-like receptor 4 signaling induces brain endothelial activation and neutrophil transmigration in vitro

Abstract: BackgroundThe innate immune response in the brain is initiated by pathogen-associated molecular patterns (PAMPS) or danger-associated molecular patterns (DAMPS) produced in response to central nervous system (CNS) infection or injury. These molecules activate members of the Toll-like receptor (TLR) family, of which TLR4 is the receptor for bacterial lipopolysaccharide (LPS). Although neurons have been reported to express TLR4, the function of TLR4 activation in neurons remains unknown.MethodsTLR4 mRNA expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(99 citation statements)
references
References 26 publications
8
91
0
Order By: Relevance
“…These results are in accordance with previous studies showing that ANG II promotes the involvement of microglia in NADPH-derived ROS in primary mesencephalic cultures (63) and that lipopolysaccharide failed to induce ROS production in bone marrow-derived macrophages cells from the same TLR4-deficient mice (67). Nonetheless, TLR4 in the brain is not exclusively expressed in microglia, and, along with AT 1a Rs, TLR4 has been shown to be also present in neurons (40,48,64). Similarly, the NADPH oxidase family, a primary source contributing to ANG II-mediated superoxide production, is present in both microglia as well as neurons (12,55,70,75,85).…”
Section: Tlr4 In Microglia Is Involved In Ang Ii-mediated Ros Within supporting
confidence: 82%
See 1 more Smart Citation
“…These results are in accordance with previous studies showing that ANG II promotes the involvement of microglia in NADPH-derived ROS in primary mesencephalic cultures (63) and that lipopolysaccharide failed to induce ROS production in bone marrow-derived macrophages cells from the same TLR4-deficient mice (67). Nonetheless, TLR4 in the brain is not exclusively expressed in microglia, and, along with AT 1a Rs, TLR4 has been shown to be also present in neurons (40,48,64). Similarly, the NADPH oxidase family, a primary source contributing to ANG II-mediated superoxide production, is present in both microglia as well as neurons (12,55,70,75,85).…”
Section: Tlr4 In Microglia Is Involved In Ang Ii-mediated Ros Within supporting
confidence: 82%
“…Taken together, our results support a major contribution of microglia and TLR4 to ANG II-mediated ROS production within the PVN. However, in addition to their presence in microglia [as shown in the present study and elsewhere (38,68)], TLR4 as well as AT 1a Rs have also been shown to be expressed in neurons (40,48,64). Thus, to further test the relative contribution of microglia versus neurons as cell targets mediating ANG II effects on PVN ROS production, we performed similar experiments in mice in which AT 1a Rs were specifically deleted from PVN neurons [(Sim1)-AT 1a KO mice; see METHODS].…”
Section: Ang Ii-mediated Ros Production Within the Pvn Is Dependent Omentioning
confidence: 89%
“…15,17 Of relevance, the expression of most of these proinflammatory molecules, including LCN2, can be upregulated through Toll-like receptor 4, 42 which is activated by LPS, but is also closely involved in the binding of extracellular Ab peptides. 43 Toll-like receptor 4 signaling cascades, which are distinct between glial cells and neurons, 44 might also explain the differences that we observe concerning the production of LCN2, a topic that warrants further investigation. Accordingly, it was recently shown that astrocytes isolated from the brain of Lcn2( À / À ) mice are unable to express the classical proinflammatory genes in response to LPS and interferon-g. 32 We observed the same kind of gene expression abrogation in Lcn2( À / À ) astrocytes after treatment with Ab , which may denote an anti-inflammatory phenotype that is conferring protection in response to these toxic peptides (Figure 7).…”
Section: Discussionmentioning
confidence: 94%
“…Another possibility is that TLRs might induce post-SCI NLRP1 inflammasome formation. Although TLRs are generally considered to be expressed in microglia and astrocytes, recent research has showed that TLR expression in neurons is pivotal under both physiological and pathological conditions [54][55][56][57]. Perhaps SCI changes expression of certain TLRs which recognize danger signals after injury and subsequently causes inflammasome formation.…”
Section: Discussionmentioning
confidence: 99%